The role of multimorbidity in suspected dementia among elderly in Shanghai, China: a community-based cross-sectional study - Tingting Zhu; Changying Wang; Yunwei Zhang; Xiaqing Wang; Yuhong Niu (Frontiers in Psychiatry, 2025)
IntroductionMany studies have shown some chronic diseases are one of the key risk factors for accelerating cognitive decline. and multimorbidity are common in the elderly population. The evidence of the impact of multimorbidity on dementia among elderly people in China is scarce in detail. This study was performed to examine the association between the prevalence of suspected dementia and multimorbidity, as well as pattern of multimorbidity among the elderly in Shanghai.MethodsThis was a cross-sectional study, with 5040 elderly individuals from 21 communities enrolled. The prevalence of suspected dementia was assessed using the Mini-Mental State Examination (MMSE). In addition, the diagnosed chronic diseases including hypertension, diabetes, hyperlipidemia and coronary heart disease (CHD) were investigated such that multimorbidity was defined as individuals suffering from two or more chronic diseases at the same time. Binary logistic regression models were utilized to analyze the impact of multimorbidity and its patterns on suspected dementia.ResultsData of 4945 older adults were analyzed. The overall prevalence of suspected dementia and multimorbidity were 15.73% and 35.98%. The influencing factors of dementia from the perspective of single disease, including diabetes, hyperlipidemia, abnormal control of blood glucose and abnormal control of blood lipid. Multivariate analysis showed multimorbidity (OR=1.491, 95%CI: 1.260-1.765) was significantly negatively associated with dementia, and the risk of dementia in elderly individuals with 2, 3 or more chronic diseases was 1.283 (95%CI: 1.058-1.555) and 2.034 (95%CI: 1.600-2.586) times greater, respectively, than those who with no multimorbidity. Notably, elderly individuals with both diabetes and hyperlipidemia had the highest risk of dementia (OR=3.253, 95%CI: 1.705-6.207).ConclusionMultimorbidity played a negative role in dementia among elderly people, dementia risk increases with the number of comorbidities, and the combination of diabetes and hyperlipidemia accentuates dementia risk at a greater level.